Family Decision-Making Pattern of Husband and Wife: an Urban Case Study in Bangladesh - Khanam, Rahima (2003)
The focus of the study was on family decision-making pattern of husband and wife. Family decision-making pattern of husband and wife was operationalised as who makes decisions and to what extent husband and wife were involved in decision-making regarding allocation of resources within the family. The study was conducted in Mymensingh district of Bangladesh. The sample of the study consisted of 60 couples with nonworking wives and 60 couples with working wives from selected areas of Mymensingh district, Bangladesh. The data were collected using the questionnaires based on 4 interview technique. In addition, qualitative data were also collected as supportive material using focus group discussion. The study found that husbands with nonworking wives had more involved in family decisions compared to their wives. Both husbands and wives of couple with working wives jointly shared decisions on family matters. The context of the research explored the variables that significantly contribute to explaining the variation of the family decision-making pattern of husbands and wives. The results of multiple regression analyses in the wives’ model showed that wives’ education and employment were found to have a positive effect on wives’ involvement in family decision-making. The results of multiple regression analyses in stepwise method also showed that for model 1 and 2, R square was 44 percent and 56 percent. Between the two (education and employment) predictor variables, wives’ education was found to contribute more significantly towards wives’ involvement in family decision-making. The husbands’ model revealed that wives’ employment and wives’ education had a negative effect on husbands’ involvement in family decisionmaking. While husbands’ gender ideology and husbands’ training had a positive effect on husbands’ involvement in family decision-making. The results 5 of multiple regression analyses in stepwise method also revealed that for model 1, 2, 3, and 4, R Square were 34 percent, 42 percent, 45 percent and 47 percent respectively. Among the four predictor variables, wives’ employment was found to contribute more significantly towards husbands’ involvement in family decision-making. These findings indicated that wives who are unemployed their husbands tend to have more involved in family decisionmaking. Access to education and training provide women with opportunities to participate in economic activities outside home, which increase their status and enhance their role to make decision regarding allocation of resources within the family. Women’s involvement in family decision-making contributes to women’s empowerment.